Narrative Identity: Formation Mechanism - Zahrai, Larysa (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses interpretations of identity from a postmodern perspective. A three-level model of personality is used to represent the methodological framework for analyzing identity. From a postmodern perspective, personal identity is defined as a socio-cultural representation. Narrative identity is formed through dialogic interaction, which results in the integration and internalization of life experience